Promoting adoption of improved seed through the Direct Seed Marketing approach - Ethiopian Agricultural Transformation Agency; International Food Policy Research Institute; Semeane, Yitbarek; Warner, James (CGIAR System Organization, 2019)
Rural transformation and poverty reduction in Ethiopia require increased agricultural productivity. Limited availability of quality seed to smallholders is a roadblock on the way to productivity growth.